Formulation and Characterization of a Dissolvable Microneedle Patch Containing Standardized Temu Mangga (Curcuma mangga) Extract for Hyperpigmentation Therapy: An In Vitro and Ex Vivo Study - Zola Efa Harnis; Indri Dwi Rahasasti; Revan Busriano Putra; Nurfitria Junita (CV. Get Press Indonesia, 2025)
Hyperpigmentation is a common skin disorder associated with Hyperpigmentation is a common skin disorder associated with excessive melanin production, while conventional topical therapies often exhibit limited efficacy due to poor skin permeability. This study aimed to develop and characterize dissolvable microneedle patches containing a standardized Curcuma mangga extract as an alternative transdermal delivery system for hyperpigmentation therapy. Three formulations (F1, F2, and F3) were prepared using varying ratios of hyaluronic acid and polyvinyl alcohol. The microneedles exhibited uniform morphology, sufficient mechanical strength, and effective skin penetration, with complete dissolution occurring within 7–15 minutes. In vitro release studies demonstrated sustained release behavior. Biological evaluation using B16-F10 melanoma cells revealed significant melanin inhibition, with formulation F2 showing the highest activity. Notably, this study is the first to integrate standardized Curcuma mangga extract into a dissolvable microneedle system and to demonstrate its combined transdermal delivery performance and antimelanogenic activity through in vitro and ex vivo evaluations. These findings indicate that Curcuma mangga-loaded microneedles represent a promising and innovative approach for hyperpigmentation therapy, warranting further in vivo investigation.